Overview of longstanding bronchial foreign bodies and role of virtual bronchoscopy - Ajith, Arun P.; Ullal, Aishwarya; Mishra, Sanjeev (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Virtual bronchoscopy (VB) is a software based, three-dimensional visualization format created from non-invasive medical imaging methods such as CT and magnetic resonance imaging, with the goal of creating views similar to minimally invasive bronchoscopy procedure. The aim of the study was to find the usefulness of VB in diagnosing vegetative and non-vegetative longstanding intra bronchial foreign bodies (FB). Methods: This was a retrospective and prospective cross-sectional study conducted in the department of otorhinolaryngology M. G. M. M. C and M. Y. hospital Indore for a period of 5 years. The medical records of patients with FB aspiration from august 2006 to September 2015 were reviewed. Data was collected regarding their clinical presentation examination and chest x-ray findings. Patients with suspected FB aspiration were subjected to VB and rigid bronchoscopy was performed. Results: In the subjects, we observed that chest radiograph were normal in as many as 40% cases. Hence negative chest radiographs do not rule out FB. In 48 patients with FB aspiration, which was detected by VB, 46 patients were diagnosed to have FB on rigid bronchoscopy. This amounts to a positive predictive value of 98%, which was similar to the gold standard, which is rigid bronchoscopy which had a positive predictive value of 99%. Conclusions: VB is the only imaging modality which gives 99.9% reassurance about the presence or absence of a FB, because of its high sensitivity and specificity, hence proves to be a lifesaving tool.